Regional Economic Development : Canada's Search for Solutions (2nd Edition) - Savoie, Donald J., 1947- (Book collections on Project MUSE., 1992)
In his widely acclaimed first edition of this book, published in 1986, Donald Savoie shed some welcome light on the Canadian experience of regional development policy. With this second edition he brings the analysis up to date.